Predicting long-term outcomes for children affected by HIV and AIDS: perspectives from the scientific study of children's development. - Stein, A; Desmond, C; Garbarino, J; Van IJzendoorn, M; Barbarin, O; Black, M; Stein, A; Hillis, S; Kalichman, S; Mercy, J; Bakermans-Kranenburg, M; Rapa, E; et al. (Lippincott Williams and Wilkins, 2014)
The immediate and short-term consequences of adult HIV for affected children are well documented. Little research has examined the long-term implications of childhood adversity stemming from caregiver HIV infection. Through overviews provided by experts in the field, together with an iterative process of consultation and refinement, we have extracted insights from the broader field of child development of relevance to predicting the long-term consequences to children affected by HIV and AIDS. We focus on what is known about the impact of adversities similar to those experienced by HIV-affected children, and for which there is longitudinal evidence. Cautioning that findings are not directly transferable across children or contexts, we examine findings from the study of parental death, divorce, poor parental mental health, institutionalization, undernutrition, and exposure to violence. Regardless of the type of adversity, the majority of children manifest resilience and do not experience any long-term negative consequences. However, a significant minority do and these children experience not one, but multiple problems, which frequently endure over time in the absence of support and opportunities for recovery. As a result, they are highly likely to suffer numerous and enduring impacts. These insights suggest a new strategic approach to interventions for children affected by HIV and AIDS, one that effectively combines a universal lattice of protection with intensive intervention targeted to selected children and families.